Seasonal patterns of oxidative stress markers in captive Asian elephants in Thailand and relationships to elephant endotheliotropic herpesvirus shedding - Kosaruk, Worapong; Brown, Janine L.; Towiboon, Patcharapa; Pringproa, Kidsadagon; Punyapornwithaya, Veerasak; Tankaew, Pallop; Kittisirikul, Narueporn; Toonrongchang, Wachiraporn; Janyamathakul, Thittaya; Muanghong, Panida; Thitaram, Chatchote (Frontiers in Veterinary Science, 2023)
Oxidative stress refers to an imbalance between oxidant and antioxidant activity and accumulation of reactive oxygen species, which can have detrimental effects on animal health. Annual fluctuations in oxidative stress status can occur, increasing disease susceptibility during certain time periods. However, a full understanding of factors related to oxidative stress in Asian elephants and how to mitigate the negative consequences is lacking. This study measured six serum oxidative stress markers (reactive oxygen species [ROS], malondialdehyde [MDA], 8-hydroxydeoxyguanosine [8-OHdG], albumin, glutathione peroxidase [GPx], and catalase) and two stress markers (serum cortisol and fecal glucocorticoid metabolites [fGCM]) in 23 captive Asian elephants in Thailand over a 12month period to examine relationships with age and season. Annual variations were observed, with several markers exhibiting significantly higher concentrations in the summer (ROS, MDA, 8-OHdG, albumin) and lower values during the rainy/winter seasons (MDA, 8-OHdG, albumin, catalase). By contrast, GPx was the only marker to be highest during the rainy season (June-July). For the stress markers, higher fGCM concentrations were noted during the rainy season, which contrasts with earlier studies showing more activity in the winter (tourist season). Positive correlations were found between THI and ROS, GPx, and fGCM, while a negative correlation was observed with serum albumin. Elephant endotheliotropic herpesvirus (EEHV) shedding events were associated with higher concentrations of ROS and MDA, although only in some elephants. A moderate negative correlation was observed between 8-OHdG and the PCR threshold cycle of EEHV shedding (Ct), indicating DNA damage may be involved in EEHV shedding in elephants. Results revealed significant age and seasonal effects on several oxidative stress markers, indicating those factors should be considered in study design and data interpretation. There also may be physiological adaptations in oxidative stress conditions in relation to environmental changes that could impact health outcomes.